Comparative analysis of the DNA isolated from thyme leaves using different methods - I. V. Bulavin; O. A. Grebennikova; V. A. Brailko; S. A. Feskov; I. V. Mitrofanova (Труды по прикладной ботанике, генетике и селекции, 2020)
Background. The base for a molecular analysis is DNA of high quality. For DNA isolation, different kits or classical methods are used. For mass analysis, isolation with kits is a very expensive process. So, the objective of our investigation was to find a cheap method for high-quality DNA isolation from leaves of various thyme cultivars.Materials and methods. Leaves cut from thyme accessions (Thymus mastichina L. cv. ‘Svetliachok’, T. striatus Vahl. cv. ‘Jubileiniy’, T. vulgaris L. cv. ‘Fantasia’, and T. vulgaris cv. ‘Jalos’.) maintained ex situ in the collection of the Nikita Botanical Gardens were used as the material for the analysis. Light microscopy was used to study leaf anatomy and localize essential oil on leaf cross sections. Essential oil was extracted on Ginsberg devices, and phenolic content was measured with The Folin–Ciocâlteu reagent (FCR). Commercial kits (DiamondDNATM, PureLink® Plant Total DNA Purification Kit) and classical methods (CTAB, CTAB with 2% polyvinylpyrrolidone) were used for DNA isolation. DNA quality was evaluated spectrophotometrically, with electrophoresis (horizontal, automated system Agilent 4200 TapeStation) and PCR.Results. The analysis showed that the leaf blade mesophyll of four thyme cultivars had inclusions with essential oil. The content of essential oil and phenolic compounds was measured biochemically. Since the plants were characterized by the presence of secondary metabolites, DNA was isolated by different methods. Spectrophotometry demonstrated that the classical CTAB method and CTAB with 2% PVP provided the best results. Using an automated electrophoresis system, the presence of high-molecularweight DNA (more than 52000 bp) in significant amounts was detected in the samples isolated with DiamondDNATM kit and CTAB + 2% PVP.Conclusion. Among the tested kits and methods, CTAB + 2% PVP provided thyme DNA suitable for PCR and, presumably, for genome library preparation. The low cost of reagents for this technique makes it applicable for future mass analysis of plant material.